After Images : Kunst als soziales Gedächtnis - Weserburg Museum für Moderne Kunst, Bremen (Bremen : Weserburg Museum für moderne kunst Bremen, 2004)
Almond, Darren ; Attie, Shimon ; Boltanski, Christian ; Chapman, Dinos & Jake ; General Idea ; Gerz, Jochen ; Herz, Rudolf ; Karnauke, Eckhard ; Korpys, Andree ; Löffler, Markus ; Kuball, Mischa ; Levinthal, David ; Prinz, Bernhard ; Rothenberg, Ellen ; Slominski, Andreas ; Tuymans, Luc ; Uklanski, Piotr ; Ullman, Micha ; Walter, Harry ; Whiteread, Rachel ; Yassour, Penny
Short biographies, literature and exhibited works p. 233-237
Duits en Engels
Exhibition "After Images : Kunst als soziales Gedächtnis", Weserburg Museum für moderne kunst Bremen. 2004-06-27. 2004-10-02
boek